2021
DOI: 10.1016/j.csbj.2021.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for complete telomere-to-telomere assembly of ciliate macronuclear genome using ultra-high coverage Nanopore data

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…Nevertheless, even with long‐read sequencing, repeat‐rich genomes yielded more fragmented assemblies (Sevim et al, 2019). While tools have been developed specially for improved scaffolding of large, repeat‐rich eukaryotic genomes (Gao et al, 2016; Miga et al, 2020; Wang et al, 2021), several long‐read metagenomic data sets already exist (Corrêa et al, 2020; Kasmanas et al, 2021; Nata'ala et al, 2022). Since short reads tend to assemble into shorter contigs compared to long reads, short‐read sequencing can influence the accuracy of gene predictions by not covering a gene's total length (Pearman et al, 2020), and single‐copy genes may not provide a realistic measure of the completeness of complex organisms such as eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, even with long‐read sequencing, repeat‐rich genomes yielded more fragmented assemblies (Sevim et al, 2019). While tools have been developed specially for improved scaffolding of large, repeat‐rich eukaryotic genomes (Gao et al, 2016; Miga et al, 2020; Wang et al, 2021), several long‐read metagenomic data sets already exist (Corrêa et al, 2020; Kasmanas et al, 2021; Nata'ala et al, 2022). Since short reads tend to assemble into shorter contigs compared to long reads, short‐read sequencing can influence the accuracy of gene predictions by not covering a gene's total length (Pearman et al, 2020), and single‐copy genes may not provide a realistic measure of the completeness of complex organisms such as eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the human reference genome is the most accurate vertebrate genome but still lacks the characterization of some chromosomes (Miga et al, 2020;Nurk et al, 2022). A study by Wang and collaborators (Wang et al, 2021), proposed a strategy for the complete assembly of two ciliates. Both studies suggest that high coverage and ultra-long nanopore sequencing may yield a better assembly of genomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, later cytochemical experiments to measure the ratio of DNA content between the MAC and MIC (23:1 at G1 phase) suggested that the amount of MAC DNA is sufficient for only 45 haploid units (Doerder & Debault, 1975; Woodard et al, 1972), based on the assumption of little difference in size between MAC and MIC genomes. However, the current version of the assembled MIC genome (157 Mb) is approximately 1.5 times larger than the MAC genome (103 Mb) (Hamilton et al, 2016; Wang, Wang, et al, 2021), corresponding to approximately 70 copies of MAC chromosomes at G1 phase. In the present study, we quantified 15 of the 180 non‐rDNA MAC chromosomes and obtained an average copy number at G1 phase of approximately 90 (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…(103 × 90.9)/(23 × 2) ≈ 204 Mb. To resolve this discrepancy, MIC genome assembly needs to be refined using long‐read sequencing technology, as was done for MAC genome assembly (Sheng et al, 2020; Wang, Wang, et al, 2021), because the current version of the assembled MIC genome contains many gaps that are likely caused by repetitive sequences (Hamilton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation